"Research ends with publication": a qualitative study on the use of health policy and systems research in Ethiopia - Sudhakar Morankar; Gelila Abraham; Zubin Shroff; Zewdie Birhanu (Health Research Policy and Systems, 2024)
Abstract Background Decision-making about the design and implementation of health care policies should be supported by research evidence. This article reports on a qualitative study on the experiences of both research institutes and policymakers in Ethiopia in generating and using research evidence to inform health policy decision-making. Methods Semi-structured interviews were conducted from January through March 2020, with representatives of research institutes and with policymakers in Ethiopia. The data collected during the interviews were analyzed thematically. Results Half of the institutions represented had engaged in health policy and systems research (HPSR). These institutes’ capacities were limited by multiple factors, including unsupportive research environments; the limited number of researchers with extensive experience; high turnover among senior researchers; lack of staff motivation mechanisms; underdeveloped research culture; limited technical and analytical capacity among researchers; lack of core funding for HPSR; ineffective financial management; and, lack of connections with health policy platforms. Research institutes also lacked the capacity in strategic packaging of findings to influence policy decision-making, although some programs have recently improved in this area. Meanwhile, there lacked a culture of using evidence in policymaking settings. In general, we found that policymakers had poor attitudes towards the quality or value of the evidence, and had little capacity to interpret evidence and apply findings to policy options. As a result, much of the research produced by the institutes have only been relevant academically, with little impact on policy. However, respondents reported that the environment is slowly changing, and the recent creation of a Research Advisory Council at the Ministry of Health offers a promising model. Conclusions Despite some recent changes, in Ethiopia researchers and policymakers alike often tend to consider health policy and systems research (HPSR) to be not very valuable since the findings generated are rarely used for evidence-informed policy development. Research institutes and researchers need to strengthen their technical, analytical, and administrative capacities (through, among other efforts, seeking more funding for research, and better incentives to attract, retain and build skills among qualified researchers); they also need to improve their understanding of the evidence-to-policy cycle and how to engage effectively with policymakers.